Verslagboek van de jaarmarkt lesbische/homostudies op 23 april 1982 - Leijten, Eduard; Sengers, Wijnand (Rotterdam : Erasmus Universiteit Rotterdam, 1982)
Fonds Suzan Daniel (FSD)
Nederlands
Monografie